Myocardial deformation in fetuses with coarctation of the aorta: a case–control study. (May 2017) - Miranda, J. O.; Hunter, L.; Tibby, S.; Sharland, G.; Miller, O.; Simpson, J. M.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 49: 565–565 ABSTRACT: Objective: To study myocardial deformation by speckle tracking echocardiography in fetuses with coarctation of the aorta (CoA) compared with gestational age‐matched normal controls. Methods: This was a retrospective study of 12 fetuses with postnatally confirmed CoA and 12 gestational age‐matched controls seen at a tertiary fetal cardiology unit between January 2013 and July 2014. Two‐dimensional speckle tracking in standard grayscale four‐chamber view of the fetal heart was performed to assess left and right myocardial deformation. Global longitudinal strain, strain rate and velocities, and regional longitudinal strain were analyzed and compared with controls. Results: Median gestational age at echocardiography was 25 + 4 weeks. Fetuses with CoA presented with a narrower, but not shorter, left ventricle when compared with controls (mitral valve diastolic diameter, 5.90 vs 8.50 mm; P = 0.002; left ventricular diastolic length, 16.50 vs 18.50 mm; P = 0.05). Global longitudinal systolic strain ( P = 0.004), systolic strain rate ( P = 0.01) and diastolic strain rate ( P = 0.004) of the left ventricle were significantly lower in fetuses with CoA compared with controls. Similar findings were observed for longitudinal systolic ( P = 0.03) and diastolic ( P = 0.01) velocities of the left ventricle. Right ventricular parameters were not different between groups. Conclusions: Fetuses with CoA have lower left ventricular longitudinal systolic strain, systolic strain rate and diastolic strain rate when compared with gestational age‐matched control fetuses. These differences in deformation might explain, at least in part, the cardiac asymmetry observed in fetuses with CoA. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.